Adolescent problem behaviors: delinquency, aggression and drug use - Marte, Ricardo M. (Criminal justice, recent scholarship, 2008)
Adolescent problem behaviors -- Theoretical framework and model development -- Testing the model : a multi-state U.S. sample -- Critical findings -- Discussion and implications